Frank O. Etheridge
1 online resource
Keywords: "This is a book by and about Frank O. Etheridge, an African-American musician from an age of cultural explosion. This manuscript, published for the first time, will be accompanied by editorial commentary written by Professor Ben Vinson III, and will be of great interest to students and scholars of African American history"--